Pemanfaatan Analitik Digital dalam Strategi Komunikasi Pemasaran Berbasis Data untuk Meningkatkan Brand Awareness Universitas di Era Digital - LM Novrianto; Jamal Ismail (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
In the digital era, universities face challenges in enhancing brand awareness amidst increasing competition. Utilizing digital analytics in data-driven marketing communication strategies becomes crucial to achieve this goal. This study aims to analyze the role of digital analytics in designing effective marketing communication strategies to boost university brand awareness. The research method employed is a literature review, gathering and analyzing various sources related to this topic. The findings indicate that integrating digital analytics enables universities to gain deep insights into audience behavior and preferences, allowing for the crafting of more targeted marketing messages. Additionally, the use of digital analytics assists in measuring the effectiveness of marketing campaigns in real-time, facilitating more responsive strategy adjustments to market dynamics. The implications of this study highlight the importance for universities to adopt digital analytics technology in their marketing communication efforts to enhance brand awareness and competitiveness in the digital age.